2009
DOI: 10.1200/jco.2008.18.7658
|View full text |Cite|
|
Sign up to set email alerts
|

First-Line Gefitinib for Patients With Advanced Non–Small-Cell Lung Cancer Harboring Epidermal Growth Factor Receptor Mutations Without Indication for Chemotherapy

Abstract: This is the first report indicating that EGFR mutation-positive patients with extremely poor PS benefit from first-line gefitinib. Because there previously has been no standard treatment for these patients with short life expectancy other than best supportive care, examination of EGFR mutations as a biomarker is recommended in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
302
1
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 468 publications
(323 citation statements)
references
References 29 publications
9
302
1
11
Order By: Relevance
“…As the introduction of first-line gefitinib in each case was dependent on the decision of the attending physician, our results may have included the clinical outcomes in elderly patients who were reluctant to receive first-line cytotoxic chemotherapy. For frail patients with EGFR-mutated NSCLC, e.g., poor PS over grade 3 or elderly (> 75 years old) with PS > 2, it was demonstrated that first-line gefitinib therapy showed a high RR (66%) and relatively long OS 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 (17.8 months) [12]. Therefore, we believe that gefitinib is a good alternative as a first-line treatment for elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…As the introduction of first-line gefitinib in each case was dependent on the decision of the attending physician, our results may have included the clinical outcomes in elderly patients who were reluctant to receive first-line cytotoxic chemotherapy. For frail patients with EGFR-mutated NSCLC, e.g., poor PS over grade 3 or elderly (> 75 years old) with PS > 2, it was demonstrated that first-line gefitinib therapy showed a high RR (66%) and relatively long OS 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 (17.8 months) [12]. Therefore, we believe that gefitinib is a good alternative as a first-line treatment for elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a greater understanding of the molecular pathways driving carcinogenesis led to the development of novel agents in NSCLC. Patients with epidermal growth factor receptor-activating (EGFR-activating) mutations or anaplastic lymphoma kinase (ALK) rearrangements have demonstrated unprecedented outcomes when treated with a first-line tyrosine kinase inhibitor (TKI) [4,[7][8][9][10][11][12][13]. Recognizing the importance of a timely and accurate diagnosis-including tumor stage, histology, and molecular subtyping-several professional societies have incorporated recommendations for biomarker testing into clinical practice guidelines for the diagnosis and management of NSCLC (Table 1) [4,7,14].…”
Section: Introductionmentioning
confidence: 99%
“…Gefitinib showed markedly better efficacy than standard chemotherapy in this subset of patients [7,8]. Deletions in exon 19 and the single L858R point mutation in exon 21 account for 90% of all EGFR mutations [1][2][3]6].…”
Section: Introductionmentioning
confidence: 99%